2018
DOI: 10.1016/j.amsu.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal adenoid cystic carcinoma, suggestion of therapeutic innovations: A case report and review of literature

Abstract: IntroductionNasopharyngeal adenoid cystic carcinoma is a rare tumor. Compared with others nasopharyngeal tumors, it is characterised by slow evolution but it is locally aggressive and has a high tendency to recurrences. Due to the rarity of cases, no consensus exists about treatment approaches.Presentation of the caseWe report the case of a 55-year-old-woman, with a locally advanced adenoid cystic carcinoma. The patient was operated by endoscopic surgery, received radiation and had a good objective response. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…At the initial treatment, a negative surgical margin should be obtained. A few studies have shown that radiotherapy might be effective in achieving local control (2,25), yet chemotherapy is ineffective for the management of secondary ACC in most cases (16).…”
Section: Discussionmentioning
confidence: 99%
“…At the initial treatment, a negative surgical margin should be obtained. A few studies have shown that radiotherapy might be effective in achieving local control (2,25), yet chemotherapy is ineffective for the management of secondary ACC in most cases (16).…”
Section: Discussionmentioning
confidence: 99%
“…Nasopharyngeal adenoid cystic carcinoma (NACC) is a rare tumor that represents approximately 1% of all carcinomas of the head and neck. NACC tends to be locally aggressive, demonstrate perineural invasion and appears ominous prognosis [7][8][9][10]. Except the type of nasopharyngeal carcinoma, overall patients with a nasopharyngeal neoplasm frequently present with at least four symptoms including nasal symptoms (epistaxis, nasal obstruction), neck masses, otological symptoms [tinnitus, deafness] and cranial nerve palsies.…”
Section: Introductionmentioning
confidence: 99%